Phytotherapy for acute respiratory tract infections in children: a systematically conducted, comprehensive review - Kamin, Wolfgang; Seifert, Georg; Zwiauer, Karl; Bonhoeffer, Jan; De Ketelaere, Veerle; D'Avino, Antonio; Štádler, Jakub; Bustamante-Ogando, Juan Carlos; Kara, Ateş (Frontiers in Pediatrics, 2025)
BackgroundThe need to reduce the inappropriate use of antibiotics for the treatment of pediatric acute respiratory tract infections (ARTIs) calls for therapeutic alternatives. The use of herbal medicines (phytopharmaceuticals) to treat ARTIs has increased worldwide. However, the evidence of phytopharmaceutical treatment, especially for children with ARTIs, has not yet been comprehensively presented.ObjectiveTo identify evidence on the efficacy and tolerability of phytopharmaceuticals in children suffering from ARTIs.MethodsWe searched the literature using two databases (PubMed and Cochrane Library) in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to identify records of clinical studies investigating the administration of phytopharmaceuticals in children with upper ARTIs (AURTIs) and/or lower ARTIs (ALRTIs).ResultsA total of 45 reports met the eligibility criteria and were included in our review. Of these, only nine reported double-blind, placebo-controlled trials investigating the efficacy and tolerability of phytopharmaceuticals in pediatric ARTIs. Overall, the included reports covered phytopharmaceuticals with the following single active ingredients: various purple coneflower (Echinacea purpurea L.) preparations, ivy (Hedera helix L.) leaf dry extract, African geranium (Pelargonium sidoides L.) root extract (EPs 7630), and pineapple fruit and stem extract preparation. In addition, various reports were included for fixed combination phytopharmaceutical products: eucalyptus oil combinations, five-herb fixed combination extract [BNO 1012 syrup], seven-herb fixed preparation [BNO 1030 solution], thyme herb and ivy leaf extracts, purple coneflower and sage leaf spray, thyme and primrose root extracts, and a preparation containing upper plant parts and roots of purple coneflower, propolis and vitamin C. The most robust efficacy and tolerability evidence available was found for EPs 7630: six double-blind, placebo-controlled trials, eight meta-analyses, four prospective open-label studies, and two observational studies, demonstrating efficacy and good tolerability.ConclusionAmong the phytopharmaceuticals identified by our systematically conducted, comprehensive literature review, EPs 7630 is supported by sufficient evidence to be regarded as an appropriate treatment to reduce the severity and duration of AURTIs and ALRTIs in children. Regarding other phytopharmaceuticals reported in the literature for the treatment of pediatric ARTIs, further research is needed to close existing evidence gaps.